2022
DOI: 10.3390/su14084577
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Knowledge Management Capabilities on Innovation Performance from Dynamic Capabilities Perspective: Moderating the Role of Environmental Dynamism

Abstract: As an important path to enhance the innovation performance of enterprises, knowledge management has received much attention in recent years. However, most of the existing literature on knowledge management and innovation performance is based on a static perspective, and ignores the influence of dynamic changes in the environment. This study intends to explore the relationship between dynamic knowledge management capability and innovation performance as well as examine the moderating effect of environmental dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 66 publications
1
7
0
Order By: Relevance
“…Analyzing the mean differences of demographic variables on moderating variables provided insights. While factors like job aspects, company establishment length, capitalization, and turnover lacked significant differences, employee count significantly influenced innovation types, consistent with prior research (Wang & Chen, 2019). Larger firms engage in radical innovations, while smaller ones prioritize incremental or process innovations due to resource constraints.…”
Section: Discussionsupporting
confidence: 80%
“…Analyzing the mean differences of demographic variables on moderating variables provided insights. While factors like job aspects, company establishment length, capitalization, and turnover lacked significant differences, employee count significantly influenced innovation types, consistent with prior research (Wang & Chen, 2019). Larger firms engage in radical innovations, while smaller ones prioritize incremental or process innovations due to resource constraints.…”
Section: Discussionsupporting
confidence: 80%
“…The moderating role of environmental dynamism has been explored at different innovation levels. For instance, it has been found to moderate the influence of innovation ambidexterity on business performance (Jansen et al, 2006;Raisch and Birkinshaw, 2008), the effect of technological capacity on innovation ambidexterity (Andrade et al, 2021), and the link between KMC and innovation performance (Feng et al, 2022). Moreover, prior research has reported that innovation exploration has strengthened firms' competitiveness when operating in dynamic rather than static environments (Chang and Gotcher, 2020;Jansen et al, 2006;Zhang et al, 2016).…”
Section: The Effects Of Environmental Dynamism and Sizementioning
confidence: 99%
“…In a dynamic environment, firms with strong knowledge capabilities may be more likely to explore and exploit innovation, as they have the knowledge, resources and expertise to adapt to changing market conditions. On the other hand, low levels of environmental dynamism may lead to a more stable and predictable environment, which may not provide as much of a stimulus for innovation (Feng et al, 2022). The moderating role of environmental dynamism has been explored at different innovation levels.…”
Section: The Effects Of Environmental Dynamism and Sizementioning
confidence: 99%
“…A firm's dynamic capabilities, which restructure and utilize its resources and capabilities in response to environmental changes, help maintain its competitive advantage and enhance its innovation performance [39,40]. Knowledge management capabilities, which have fundamentally dynamic characteristics, have a positive impact on product/process innovation by capturing necessary knowledge from a firm's internal and external sources and converting it into productive outcomes [41,42]. Knowledge management can promote the creation of new ideas and ultimately improve R&D performance by facilitating the exchange and sharing of knowledge necessary for R&D [43].…”
Section: B Randd Failure and Survival Of Smesmentioning
confidence: 99%